Research on the influence mechanism and governance mechanism of digital divide for the elderly on wisdom healthcare: The role of artificial intelligence and big data - Zhou, Jian; Wang, Zeyu; Liu, Yang; Yang, Jian (Frontiers in Public Health, 2022)
As the rapid development of digital information technology, life has become more convenient for people, however, the digital divide for the elderly was even more serious, so they became a forgotten group in the internet age over time. Residents' demand for health care is rising, but the wisdom health care service supported by digital information technology is less acceptable to the elderly due to the digital divide. Based on the knowledge gap theory and combining the value perception and satisfaction model, this paper explores the influence of the digital divide for the elderly on wisdom health care satisfaction, and takes perceived value of wisdom health care as a mediator, and artificial intelligence and big data as moderators into the research framework. Based on the data of 1052 elderly people in China, the results show that the digital divide for the elderly has a negative influence on wisdom health care satisfaction and perceived value. Besides, it is found that wisdom health care perception value mediated the relationship between digital divide for the elderly and the wisdom health care satisfaction, which enhances the negative effect of the digital divide for the elderly on wisdom health care satisfaction. Furthermore, the moderating effect of artificial intelligence and big data on the relationship between digital divide for the elderly and perceived value of wisdom health care is opposite to that between perceived value of wisdom health care and wisdom health care satisfaction. Therefore, this study has reference value for the development and optimization of smart medical industry.